AUDIT SISTEM INFORMASI PENJUALAN BARANG PADA PT ALLWARES SOLUTIONS MENGGUNAKAN METODE FRAMEWORK COBIT - ., Angellina; Sari, Intan Utna (Computer Science and Industrial Engineering, 2021)
In general, every company has buying and selling transactions of goods to consumers. PT Allwares Solutions, which is a company engaged in general supplier selling ship engines, spareparts and industrial equipment in Batam, has been implementing information systems related to sales. This company already has a sales information system using GF Accounting. However, it’s not known that there are problems in the system because there are frequent errors in the system because the location of the GF Accounting placement isn’t read by the system, and items are exchange for other items due to inaccurate data management. In addition. The purpose of this research is to see the maturity level of the sales information system at PT Allwares Solutions by using COBIT 4.1 the authors use the framework of COBIT 4.1 with a focus on the DS domain which consists of the DS1, DS3, DS4 and DS5 domains. The results of the analysis of the level of maturity show that the information system regarding sales at PT Allwares Solutions is at level 3 with a process that is determined by status, which means that PT Allwares Solutions has accurately measured the allocation of IT costs for the company's business.